Psychological approaches to the problem of labor safety - Ph.D. Associate Professor Yuldashev Orunbai Rakhmonberdievich; Abdurakhmanova Sayyorakhon Ruzalievna (Zien Journals, 2022)
The article deals with the psychological foundations for the development and implementation of an effective labor protection management system at an enterprise in the process of professional training. Existing psychological approaches to the study and solution of the problem of safe labor are analyzed. Their importance in the development of a modern perspective approach to this problem is shown. An attempt was made to substantiate the constructiveness of a systematic approach based on the concept of organizational culture. An assumption is made about the need to develop this modification of the system approach, taking into account the system-evolutionary concept of personality and cultural-historical theory.
Keywords: labor safety; medical and psychological approach; psychotechnical approach; systemic approach